Faktor Predisposisi yang Mempengaruhi Karies Gigi pada Anak Usia Sekolah Dasar Di SDN Marengan Laok I Kabupaten Sumenep - Zakiyah Yasin; Imam Muslim; Achmad Haryono Budiyantoro (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2020)
Dental and oral health is a part of general health that needs to be considered by people and need comprehensive treatment because the impact is so wide that it needs immediate treatment before it is too late. To know the factors that influence dental caries in elementary school age children of Grade 3 at SDN Marengan Laok I Kalianget District Sumenep Regency. The design of this research using correlational analytic method. The sampling method used NonProbability sampling type of total population of 30 respondents. This research data is taken using questionnaire which then result is tabulated and analyzed by using SPSS v16 Chi-Square statistical test with trust level 0,05. The data that have been processed then presented in the form of tables and narration. The results showed that dental caries in elementary school-aged children were based on factors of time and frequency of brushing most of the teeth (57%), dental caries based on tooth brushing factor (53%), and dental caries based on most dental care factors (53 %). The value of SPSS in both factor factor of tooth brushing and dental technique is 0.000 and 0,002 which means <0,05 then H1 accepted means on the factor of treatment technique affect dental caries in elementary school age child of Grade 3 at SDN Marengan Laok Kalianget Sumenep Regency. The results of this study indicate that the role of parents and the school is very necessary in providing health information about dental caries and how to brush your teeth with the correct technique in order to avoid dental caries.